THE EFFECT OF CONCENTRATE CONTAINING PROBIOTICS ON FERMENTATION CHARACTERISTICS, METHANOGENESIS AND In vitro NUTRIENT DIGESTILITY - Santoso, B.; Hariadi, B. Tj.; Abubakar, H. (Diponegoro University, 2014)
The aim of the experiment was to evaluate the effect of probiotic addition in concentrate onfermentation characteristics, methane (CH4) production and in vitro nutrient digestibility. Two strainslactic acid bacteria (LAB) i.e. Lactobacillus plantarum and Lactobacillus acidhophilus, and one strainyeast of Saccharomyces cerevisiae was used as probiotic.This experiment was arranged in a completelyrandomized design consisted of 4 treatments as follows grass silage (G); grass silage + concentratewithout probiotic (G+A); grass silage + concentrate containing L. plantarum and. S. cerevisiae (G+B);grass silage + concentrate containing L. acidophilus and. S. cerevisiae (G+C); grass silage + concentratecontaining L. plantarum and L. acidophilus (G+D). Data were analyzed as completely randomizeddesign and followed by Duncan’s multiple range test. The results showed that the concentrate containingLAB varied 1.5 × 106 and 3 × 107 cfu/g, and 3 × 103 cfu/g of S. cerevisiae. Combination between L.plantarum and S. cerevisiae (G+B), and L. acidophilus and S. cerevisiae (G+C) in concentrate increased(P<0.01) propionic acid proportion. The average CH4 production in concentrate containing probiotic(G+C, G+D and D+E) was lower by 6.9% (P<0.01) compared to concentrate without probiotic (G+B). The in vitro dry matter (DM) and neutral detergent fiber (NDF) digestibility were higher (P<0.01) by25.7% and 6.3% respectively, in grass silage substrate with concentrate containing probiotic (G+C, G+Dand G+E) than in grass silage with concentrate without probiotic (G+B). In conclusion, addition ofprobiotic in concentrate could increase in vitro propionic acid proportion, DM and NDF digestibility andreduce CH4 production.